Dampak Pengembangan Ekowisata Hutan Mangrove Terhadap Ekonomi Masyarakat Desa Watubaing TWAL Gugus Pulau Teluk Maumere - Saveria Novi Triana; Fadlan Pramatana; Roni Haposan Sipayung (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Mangrove forests provide environmental benefits by maintaining the balance of coastal ecosystems, protecting shorelines from abrasion, processing toxic waste, producing oxygen, absorbing carbon dioxide, and serving as habitats and food sources for other living beings. Mangrove forests also contribute to the community's economy, one of which is through tourism, such as ecological tourism or more commonly known as ecotourism. This research was conducted in August 2024 in the Conservation Area of the Marine Nature Tourism Park (Taman Wisata Alam Laut or TWAL). The selection of respondents in this study used a purposive sampling technique. The characteristics of the respondents who served as key informants in this study included area managers, community groups, and local residents around the mangrove ecotourism area who run businesses. The data analysis methods used in this study were descriptive analysis and multiple linear regression analysis. The research results show that the F-test and t-test analysis obtained an F-count smaller than the F-table (F-count = 2.530 < F-table = 3.10), indicating thet all the independent variables used do not have a significant relationship with the dependent variable. Furthermore, based on the t-test analysis, the variables of business opportunity (X1) and management (X3) had t-count values smaller than the t-table (t-count for X1 and X3 = -0.682 and 0.504 < t-table = 2.080), indicating that the independent variables X1 and X3 do not have a significant effect on the community’s economic variable (Y). Meanwhile, the t-count value for the labor absorption variable (X2) was greater than the t-table (t-count X2 = 2.303 > t-table = 2.080), indicating that the X2 variable has a significant effect on the community’s economic variable (Y).